Social Network Sites: Modeling the New Business-Customer Relationship - Isaias, Pedro; Pifano, S.; Miranda, P. (IGI Global, 2011)
The internet and the emergence of social technologies and platforms are at the origin of new consumer trends. The growing empowerment of customers is having a restructuring impact in business-consumer relationships and it is pressing businesses to uncover new strategies to engage their clients. This chapter argues that the presence of the corporate sector in Social Network Sites (SNSs) presents a successful method of building proficient relationships with customers that are more compliant with the new facets of consumers’ profile and behaviour. This research crosses classical academic literature with case studies available in social media to gather a compilation of challenges and potential solutions to the application of SNSs to business-consumer relationships. This compilation is preceded by an introductory section, which explores the definition and possible applications of SNSs in business, and a section dedicated to an overview of the novel consumer trends.